Driving Factors for Learner Engagement in MOOCs: An Interpretive Structural Modeling Approach - Garg, Girish; Rani, Mala (Indian Journal of Educational Technology, 2025)
The impact of technology on education has revolutionized the way we teach and learn. It has widened the scope of education, making it more accessible, efficient, and effective. With the help of technology, learners can learn through various online platforms, breaking the traditional classroom barriers. This has resulted in a global learning community connecting learners from different parts of the world. The Indian government launched an initiative called SWAYAM in August 2014, which provides Massive Open Online Courses (MOOCs) to promote equal access to quality education. These courses are gaining popularity and are easily accessible to anyone with an internet connection. SWAYAM offers courses in higher education, high school, and skill sectors. This program enables learners to earn credits recorded in their academic bank of credits (ABC) to advance their careers. Variables such as curiosity, reputation, flexibility, and intention play a crucial role in driving the other variables in the final model. The study’s dependent variables include credit transfer, assistance, mentor-mentee support, job prospects, and eagerness. To create MOOC courses for learners, universities and institutes must consider important factors that are crucial in today’s world.